Dogmatic and Scientific Analysis of Akhlak Education Implementation at MTs Tarbiyatul Qurro' - Suparman Suparman; Fathurrahmanmuhtar Fathurrahmanmuhtar (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
This study aims to analyze the implementation of moral learning at MTS Tarbyatul Qurro with a dogmatic and scientific approach. The main focus of this study is to explore the application of moral values ​​based on Islamic teachings and evaluate the effectiveness of learning methods used in the school context. This study uses a qualitative approach with a case study method, where data is collected through in-depth interviews, observations, and documentation. The results of the study indicate that moral learning at MTS Tarbyatul Qurro is based on strong Islamic teaching principles and is supported by interactive teaching methods that are relevant to students' lives. However, several challenges were found in its implementation, especially in terms of internalizing moral values ​​by students outside the school environment. This finding indicates the importance of synergy between formal education and the habituation of moral behavior in the family and society. In conclusion, the dogmatic and scientific approaches to moral learning at MTS Tarbyatul Qurro have been successfully implemented, although it requires more effort in implementing morals holistically in students' lives.